2019
DOI: 10.1002/da.22960
|View full text |Cite
|
Sign up to set email alerts
|

Gender commonalities and differences in risk and protective factors of suicidal thoughts and behaviors: A cross‐sectional study of Spanish university students

Abstract: Aim: To assess gender differences in the association between risk/protective factors and suicidal thoughts and behaviors (STB); and whether there is any genderinteraction with those factors and STB; among Spanish university students.Methods: Data from baseline online survey of UNIVERSAL project, a multicenter, observational study of first-year Spanish university students (18-24 years). We assessed STB; lifetime and 12-month negative life-events and family adversities; mental disorders; personal and community f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…In this context of severity, gender differences are more difficult to demonstrate compared to community samples. Furthermore, this result is in agreement with the recent study by Miranda-Mendizabal et al (52) which showed that mood disorders are the only risk factors for suicidal thoughts that are common to both sexes. We found differences in SA patterns that have been widely reported by other teams (4,5,25).…”
Section: Discussionsupporting
confidence: 93%
“…In this context of severity, gender differences are more difficult to demonstrate compared to community samples. Furthermore, this result is in agreement with the recent study by Miranda-Mendizabal et al (52) which showed that mood disorders are the only risk factors for suicidal thoughts that are common to both sexes. We found differences in SA patterns that have been widely reported by other teams (4,5,25).…”
Section: Discussionsupporting
confidence: 93%
“…Thus, 245 articles were selected for full-text reading, of which two were not available for access, resulting in 243 articles for full reading. After analyzing the eligibility criteria, 232 studies were excluded, resulting in 11 articles that comprised this review (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) . Figure 2 presents the flowchart corresponding to the results of the search, selection and inclusion of studies, as well as the reasons for the excluded studies.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, two surveys did not report the percentage of participants who answered the research instruments (27)(28) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations